Storytelling Sebagai Metode Pembelajaran Maharah Kalam - Azhari, Irsad; Muassomah, Muassomah (STIQ Amuntai, 2024)
Storytelling is a learning method that provides stimulation for students to interact through stories. The research aims to analyze the implementation, advantages and disadvantages, as well as supporting and inhibiting factors of storytelling as a maharah kalam learning method at MA Muallimin Al-Huda Jombang. This research uses a descriptive qualitative approach with the type of field research. Data collection techniques using observation, interviews and documentation. Data analysis uses the analytical techniques of Mattew B. Milless and A. Michael Hubermen, including data correction, data reduction, data presentation, and verification or drawing conclusions. The research results show that storytelling is effective and efficient in improving the quality of students' maharah kalam learning. The advantages of this method include increasing motivation, interaction, cooperation, self-confidence, making stories more lively, making it easier to understand the material, and enriching vocabulary. However, the drawback is that if the teacher is less expressive, students can lose focus, get bored or sleepy. Supporting factors for this method are teacher enthusiasm, interesting stories, the teacher's ability to present stories, adequate learning resources, a conducive environment, and sufficient facilities and infrastructure. Inhibiting factors include limited time, teachers' difficulties in conveying interesting stories, students' lack of ability to read texts, students' lack of attention, and differences in students' levels of understanding.